Spatial Analysis of Risk Factors for Dengue Fever in Delta Pawan District, Ketapang Regency - Rasyid, Khairul; Raharjo, Mursid; Nurjazuli, Nurjazuli (Griya Eka Sejahtera, 2025)
Background: Delta Pawan District in 2023, there were 388 cases of DHF (IR 424,3/100.000 population) with a mortality rate of 2 cases (CFR 0,25%). Dengue fever is still a public helath problem in Delta Pawan District every year. Comprehensive control effort are needed to control dengue fever, one of which is by identifying risk factors for dengue fever in The Delta pawan District area. This study aimed to identify relationships between the existence of positive breeding places for mosquito larvae and the habit of cleaning water reservoirs with the incidence of dengue fever.Method: This study uses an analytical observational approach with a method Cross Sectional, using Geographic Information System (GIS) to identify and analyze the occurrence of dengue fever and risk factors. The number of samples used was 142 samples (71 case samples and 71 control samples).Results: Based on statistical analysis, it was found that there was a relationship between the existence of positive breeding places for larvae and the incidence of DHF in Delta Pawan District, P-value 0.000 OR 6.462. There was a relationship between the habit of cleaning water reservoirs and the incidence of DHF P-value 0.002 OR 3.044. There was no relationship between the habit of hanging used clothes and the incidence of DHF in Delta Pawan District. The distribution pattern of DHF cases in Delta Pawan District in 2024 based on Moran's I autocorrelation analysis is random.Conclusion: There is a relationship between the existence of positive breeding places for mosquito larvae and the habit of cleaning water reservoirs with the incidence of dengue fever.